Characteristics of Pediatric Tuberculosis Patients at Simpang Lima Gumul Hospital, Kediri, East Java - Rika Oktania Sari; Bayu Prabowo (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Pediatric tuberculosis can cause a variety of problems, including growth failure, disability, and death. In 2021, WHO recorded 10.6 million individuals had tuberculosis globally, with pediatric tuberculosis accounting for 11% of these cases. Indonesia is the second highest high-burden country for tuberculosis, according to the WHO. Children with tuberculosis often present non-specific and uncommon symptoms, making diagnosis challenging and frequently delayed. This study aims to present an overview of the characteristics of pediatric tuberculosis patients at Simpang Lima Gumul Hospital in Kediri, East Java. Material and Methods: This was a descriptive retrospective study with a cross-sectional method. Pediatric tuberculosis patients who received treatment at the Simpang Lima Gumul Hospital in Kediri, East Java, were the subject of research. We compiled pediatric tuberculosis patients' demographic data and clinical characteristics using medical records. Results: Sixty-one children included in the study. Most of them were male (56%) between 1 to 5 years old (52%). Seventy-two percent had a positive tuberculin skin test; chronic cough was noted in 69% of cases. An adult contact history of tuberculosis was reported in 64% of cases, while 61% had radiographic findings from TB. 52% also had fever, 51% had lymphadenopathy, and 72% had good nutritional status. Conclusion: Tuberculosis occurs most commonly in male children 1 to 5 years of age. The most common symptoms of pediatric tuberculosis include a positive tuberculin skin test, chronic cough, contact with adults with tuberculosis, positive radiographic findings, fever, and lymphadenopathy.